2016
DOI: 10.5935/abc.20160131
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Strain and Strain Rate: A Novel Method for the Evaluation of Atrial Stunning

Abstract: BackgroundAtrial fibrillation (AF) is the most common arrhythmia seen in adults. Atrial stunning is defined as the temporary mechanical dysfunction of the atrial appendage developing after AF has returned to sinus rhythm (SR).ObjectivesWe aimed to evaluate atrial contractile functions by strain and strain rate in patients with AF, following pharmacological and electrical cardioversion and to compare it with conventional methods.MethodsThis study included 41 patients with persistent AF and 35 age-matched contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Some previous studies that used conventional echocardiographic parameters also showed that the maximum improvement in atrial function was observed at the end of the first month [20, 21]. Meanwhile Ozkan H et al used strain analysis and demonstrated that atrial stunning can last longer than 1 month and it depends on AF duration [22]. Several studies have proven elevated plasma NPs concentrations in most patients with AF and significant drop following SR restoration by ECV, radiofrequency catheter ablation, or pulmonary vein isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies that used conventional echocardiographic parameters also showed that the maximum improvement in atrial function was observed at the end of the first month [20, 21]. Meanwhile Ozkan H et al used strain analysis and demonstrated that atrial stunning can last longer than 1 month and it depends on AF duration [22]. Several studies have proven elevated plasma NPs concentrations in most patients with AF and significant drop following SR restoration by ECV, radiofrequency catheter ablation, or pulmonary vein isolation.…”
Section: Discussionmentioning
confidence: 99%
“…The damage incidence of LAA function is directly proportional to the incident rate of embolic diseases in AF patients [9], and the mechanical function of LAA is closely related to the therapeutic effect of treatments for AF [10]. In the ventricular systole, the active relaxation activities and stiffness of LA will affect the volume of circulating heart blood flow from the pulmonary vein to the LA [11]. The functions of LA and LAA associate with the therapeutic effect of treatments for AF, therefore, the accurate evaluation of LA and LAA possesses significant meanings to estimate the AF illness state, including helping clinical doctors make accurate judgment, formulate effective therapeutic plans and evaluate the therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…После восстановления синусового ритма любым способом (спонтанная, медикаментозная или электрическая кардиоверсия), развивается феномен "оглушения" или станинга, который представляет собой механическую дисфункцию миокарда обоих предсердий и может сохраняться от нескольких дней до 3-4 нед. и более в зависимости от продолжительности аритмии, структурного ремоделирования предсердий [11].…”
Section: результаты и обсуждениеunclassified